Jan Lebenstein i Galerie Lambert w 1959 roku. Okoliczności pierwszej wystawy - Banaszak, Marta; Supruniuk, Mirosław Adam (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2013)
JAN LEBENSTEIN AND GALERIE LAMBERT IN 1959. THE CIRCUMSTANCES OF THE FIRST EXHIBITION In 1959, Jan Lebenstein, a distinguished painter had his first two exhibitions in Paris. The featured correspondence between the painter, Galerie Lambert in Paris, Kazimierz Romanowicz and Konstanty A. Jeleński sheds light on the circumstances of those exhibitions and the problems faced by Polish visual artists during the Cold War.